Case Report: TNF-Alpha Inhibitors to Rescue Pregnancy in Women With Potential Pregnancy Loss: A Report of Ten Cases - Zhong, Zixing; Wang, Yuhan; Wang, Guiqin; Zhou, Feifei (Frontiers in Immunology, 2022)
Miscarriage is prevalent and poses a significant threat to childbearing age women globally. Recurrent miscarriages or potential poor embryonic development indicated by early fall of serum human chorionic gonadotrophin (hCG) were even more catastrophic for pregnant women. However, they received either individualized medical intervention supported by limited evidence or nothing. In this study, we report ten patients who similarly share at least one episode of an early decline of hCG in the first trimester and were treated with compassionate use of tumor necrosis factor-alpha inhibitor (TNFi). They were then followed up regularly with caution. Their hCG trajectory all resumed normal pattern within one week and the obstetric outcomes were surprised by far. No adverse fetal, neonatal or maternal health compromise has been observed. This case series support current safety evidence of TNFi and provide new insight into its use in pregnancy when the embryo is in danger. Further well-designed clinical trials should be carried out to consolidate the evidence.